PENGATURAN TERHADAP STATUS PERMOHONAN YANG DIDIAMKAN OLEH BADAN DAN / ATAU PEJABAT TATA USAHA NEGARA MENURUT UU PTUN DAN UU AP - Riza, Dola (Normative Jurnal Ilmiah Hukum, 2022)
The Status of Applications Silenced by State Administrative Agencies and/or Officials has been regulated in the Administrative Court Law. After the promulgation of the Government Administration Law, the Status of Applications Silenced by State Administrative Agencies and/or Officials is also regulated in the Government Administration Law, but there are differences in the arrangements for the Status of Applications Silenced by State Administrative Agencies and/or Officials. The formulation of the problem in this study is how to regulate the Status of Silenced Applications by State Administrative Agencies and/or Officials according to the Law on State Administrative Court Law and the Government Administration Law. The type of research used is normative legal research. The research approach used is a statutory approach and a conceptual approach. The legal materials used are primary legal materials, secondary legal materials and tertiary legal materials. The legal material collection technique used is document study. The legal material analysis technique used is a qualitative analysis technique. Based on the results of the study, it can be concluded that the regulation regarding the status of applications that are silenced by the State Administrative Agency and/or Officials, which was previously negatively fictitious, but after the issuance of the Government Administration Law became positively fictitious. Even though there are differences, the arrangements for material law are guided by the Government Administration Law and formal law is still guided by the Administrative Court Law.